Effect Of Substitution Of Black Glutinous Rice Flour On The Quality Of Baked Brownies - Hanifah Indra Fansyukri; Wirnelis Syarif (Universitas Negeri Padang, 2021)
The background of this research is the high value of wheat imports and increasing the use of local food ingredients, namely black glutinous rice flour in food processing. This study aims to analyze the effect of substitution of 30%, 40% and 50% black glutinous rice flour on the quality of baked brownies which include shape, color, aroma, texture and taste. The type of research is a true experiment with three repetitions carried out in July 2021 at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The type of data is primary data sourced from 3 expert panelists by answering the organoleptic test format. The data were analyzed by ANOVA statistical analysis, if Fcount > Ftable, it was continued with Duncan's test. The results showed that there was no effect of substitution of black glutinous rice flour on the quality (shape, color, chocolate aroma, texture, sweetness and chocolate taste) of baked brownies, meanwhile there was an effect of substitution of black glutinous rice flour on the quality (aroma of glutinous rice flour). black and black glutinous rice flour flavor) baked brownies. The best results based on the organoleptic test were found in X0 and X2 with 40% black glutinous rice flour substitution.